2007
DOI: 10.1196/annals.1392.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FLT3 Inhibition on Normal Hematopoietic Progenitor Cells

Abstract: Ligand-mediated activation of the FMS-like tyrosine kinase-3 (FLT3) receptor is important for normal proliferation of primitive hematopoietic cells. FLT3 expression in the bone marrow is restricted to CD34(+) cells and a subset of dendritic precursors. FLT3, as a member of the type III RTK subfamily, is closely related to c-kit, c-FMS, and PDGFalpha/beta and is an unspecific target of tyrosine kinase inhibitors, such as imatinib. Activating mutations of FLT3 play an important role in leukemogenesis and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…These pathways most likely play critical roles in the development of anemia. One explanation for anemia with multitargeted TKIs is the action on hematopoiesis of FLT-3 and Kit blockade [20,88,89]. This probably explains some forms of macrocytosis seen during sunitinib therapy and mentioned previously [16 -20].…”
Section: Discussionmentioning
confidence: 82%
“…These pathways most likely play critical roles in the development of anemia. One explanation for anemia with multitargeted TKIs is the action on hematopoiesis of FLT-3 and Kit blockade [20,88,89]. This probably explains some forms of macrocytosis seen during sunitinib therapy and mentioned previously [16 -20].…”
Section: Discussionmentioning
confidence: 82%
“…19,20 Furthermore, it has previously been shown that plasma FL levels rise during periods of bone marrow aplasia induced by chemotherapy or radiation. [21][22][23][24][25][26][27] Given that in both of these trials lestaurtinib was administered after intensive chemotherapy, we decided to examine FL levels in the plasma samples available to us.…”
Section: Plasma Flt3 Ligand Levels Are Elevated After Chemotherapymentioning
confidence: 99%
“…In line, we also found decreased transcriptional activity of molecules involved in the maintenance of stem-cell fate such as FLT3 and PTEN (Table 1). Inhibition of FLT3 led to a reduction of the stem-cell pool 33 and inactivation of PTEN caused long-term decline of HSC fostering differentiation and proliferation 34 in murine models. Accordingly, gene expression levels of CD133 were lower in CML HSC compared their normal counterparts.…”
Section: The Hsc Subset Of Patients With CML Shows Impaired Migratorymentioning
confidence: 99%